Unrecognized Emergence of Chikungunya Virus during a Zika Virus Outbreak in Salvador, Brazil. - Cristiane W Cardoso; Mariana Kikuti; Ana Paula P B Prates; Igor A D Paploski; Laura B Tauro; Monaise M O Silva; Perla Santana; Marta F S Rego; Mitermayer G Reis; Uriel Kitron; Guilherme S Ribeiro (Public Library of Science (PLoS), 2017)
BACKGROUND:Chikungunya virus (CHIKV) entered Brazil in 2014, causing a large outbreak in Feira de Santana, state of Bahia. Although cases have been recorded in Salvador, the capital of Bahia, located ~100 km of Feira de Santana, CHIKV transmission has not been perceived to occur epidemically, largely contrasting with the Zika virus (ZIKV) outbreak and ensuing complications reaching the city in 2015. METHODOLOGY/PRINCIPAL FINDINGS:This study aimed to determine the intensity of CHIKV transmission in Salvador between November 2014 and April 2016. Results of all the CHIKV laboratory tests performed in the public sector were obtained and the frequency of positivity was analyzed by epidemiological week. Of the 2,736 tests analyzed, 456 (16.7%) were positive. An increasing in the positivity rate was observed, starting in January/2015, and peaking at 68% in August, shortly after the exanthematous illness outbreak attributed to ZIKV. CONCLUSIONS/SIGNIFICANCE:Public health authorities and health professionals did not immediately detect the increase in CHIKV cases, likely because all the attention was directed to the ZIKV outbreak and ensuing complications. It is important that regions in the world that harbor arbovirus vectors and did not experience intense ZIKV and CHIKV transmission be prepared for the potential co-emergence of these two viruses.